Maternal pregnancy-induced hypertension increases subsequent neonatal necrotizing enterocolitis risk: A nationwide population-based retrospective cohort study in Taiwan. Issue 31 (August 2018) - Yang, Chih-Chieh; Tang, Pei-Ling; Liu, Po-Yen; Huang, Wei-Chun; Chen, Ying-Yao; Wang, Hsiao-Ping; Chang, Jenn-Tzong; Lin, Li-Te
Abstract : Abstract: The utero-placental ischemia induced by pregnancy-induced hypertension (PIH) could lead to fetal hypoxia and proinflammatory cytokine release, which are associated with the development of neonatal necrotizing enterocolitis (NEC). However, a few studies have investigated the relationship between PIH and neonatal NEC and have produced controversial results. Therefore, we attempted to assess the relationship between PIH and the subsequent neonatal NEC risk and identify predictive risk factors. Patients with newly diagnosed PIH were recruited from the Taiwan National Health Insurance Research Database (NHIRD). For each participant, 4 age- and delivery-year-matched participants without PIH were randomly selected. A multivariable logistic regression was performed for the identification of the predictive risk factors for neonatal NEC. Among the 23.3 million individuals registered in the NHIRD, 29, 013 patients with PIH and 116, 052 matched controls were identified. For the multivariable analysis, maternal PIH was associated with an increased risk of subsequent neonatal NEC development (odds ratio [OR] 1.86, 95% confidence interval [CI] 1.08–3.21, P  = .026). Furthermore, single parity (OR 2.06, 95% CI 1.12–3.77, P  = .019), preterm birth (OR 5.97, 95% CI 3.49–10.20, P  < .001), multiple gestations (OR 2.25, 95% CI 1.22–4.14, P  = .010), and intrauterine growth restriction (IUGR) (OR 3.59, 95% CI 2.06–6.24, P  < .001) were independent risk factors for the development of subsequent neonatal NEC. Maternal PIH increases the risk for developing neonatal NEC. Furthermore, primiparity, preterm birth, multiple gestations, and IUGR were independent risk factors for neonatal NEC.